Case Report: Slow-Flow Venous Malformation In The Breast: A Case Report With Extended Chest Wall Involvement (The Review of Diabetic Studies, 2024)
Introduction: Vascular abnormalities in the breast are rare and include various conditions such as congenital malformations and tumors like hemangiomas, lymphangiomas, and angiosarcomas. These conditions can often be mistaken for breast cancer due to similar clinical and imaging features(6) . The identification of a venous malformation in a despite its rarity in breast tissue, emphasizes the necessity for radiologists to maintain a high index of suspicion for vascular anomalies when interpreting imaging results.The imaging modalities utilized including mammography, ultrasound ,and MRI provided comprehensive insights into the nature of the lesions, allowing for a nuanced understanding of their characteristics. (Pdf eurorad) This case report examines a rare presentation of a slow-flow venous malformation in the left breast and anterolateral chest wall, emphasizing the importance of multimodal imaging for accurate diagnosis and management.Case Presentation: A 79-year-old female presented with a progressively enlarging left breast mass with peau d'orange appearance. Imaging studies including ultrasound, CT, MRI, and angiography, confirmed a large slow-flow venous malformation with multiple thrombosed venous lakes extending into the chest wall and upper limb. No evidence of malignancy was noted. The patient had associated conditions including thrombosis of the left axillary vein and pleural effusion.Conclusion: This case underscores the importance of thorough imaging evaluation in diagnosing slow-flow venous malformations and the necessity of a multidisciplinary approach for optimal management.